Pharmacokinetic Interactions between Cardiovascular Medicines and Plant Products - Irina-Iuliana Costache; Anca Miron; Monica Hăncianu; Viviana Aursulesei; Alexandru Dan Costache; Ana Clara Aprotosoaie (Cardiovascular Therapeutics)
The growing use of plant products among patients with cardiovascular pharmacotherapy raises the concerns about their potential interactions with conventional cardiovascular medicines. Plant products can influence pharmacokinetics or/and pharmacological activity of coadministered drugs and some of these interactions may lead to unexpected clinical outcomes. Numerous studies and case reports showed various pharmacokinetic interactions that are characterized by a high degree of unpredictability. This review highlights the pharmacokinetic clinically relevant interactions between major conventional cardiovascular medicines and plant products with an emphasis on their putative mechanisms, drawbacks of herbal products use, and the perspectives for further well-designed studies.